2004
DOI: 10.1021/ja049376t
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transition-State Stabilization in Enzyme Catalysis:  Quantum Chemical Analysis of Interactions in the Chorismate Mutase Reaction and Prediction of the Optimal Catalytic Field

Abstract: Chorismate mutase is a key model system in the development of theories of enzyme catalysis. To analyze the physical nature of catalytic interactions within the enzyme active site and to estimate the stabilization of the transition state (TS) relative to the substrate (differential transition state stabilization, DTSS), we have carried out nonempirical variation-perturbation analysis of the electrostatic, exchange, delocalization, and correlation interactions of the enzyme-bound substrate and transition-state s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
177
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(195 citation statements)
references
References 69 publications
14
177
2
2
Order By: Relevance
“…It was found that significant orbital overlap between the substrate and a number of charged active site residues act to stabilise the transition state (relative to the reactant and product states). This picture is supported by a previous study, which demonstrated the importance of electrostatic interactions in the active site to TS stabilisation in chorismate mutase [225].…”
Section: Chorismate Mutasesupporting
confidence: 83%
“…It was found that significant orbital overlap between the substrate and a number of charged active site residues act to stabilise the transition state (relative to the reactant and product states). This picture is supported by a previous study, which demonstrated the importance of electrostatic interactions in the active site to TS stabilisation in chorismate mutase [225].…”
Section: Chorismate Mutasesupporting
confidence: 83%
“…1). Furthermore, differential transition state stabilization (DTSS) analysis, 14 an emerging approach for identifying important interactions in enzyme-catalysed reactions, 15 was also performed to identify crucial residues involved in FAAH inhibition.…”
mentioning
confidence: 99%
“…Fortunately, the redistribution of molecular charge density can also be monitored more directly through the multipole expansion of any well-defined molecular property, such as the MEP or electric fields. In their case, the arbitrary character of a particular atomic charge definition is, to a large degree, eliminated, yielding static or dynamic catalytic fields [2] and aiding de novo catalyst design.…”
Section: Convergence Of Moment-derived Molecular Electrostatic Potentmentioning
confidence: 99%
“…Finally, we turn to two reactions involving neutral reactants, namely the second phase of the reaction of CO 2 with water during which a CO double bond is formed (Fig. 6) and the isomerisation of HCN to HNC (Fig.…”
Section: Convergence Of Moment-derived Molecular Electrostatic Potentmentioning
confidence: 99%
See 1 more Smart Citation